1994
DOI: 10.1111/j.1432-1033.1994.tb18769.x
|View full text |Cite
|
Sign up to set email alerts
|

The complete amino acid sequence of R‐phycocyanin‐I α and β subunits from the red alga Porphyridium cruentum

Abstract: We present here the complete primary structure of R-phycocyanin-I a and p subunits from the red alga Porphyridium cruentum. The a chain is composed of 162 amino acid residues (18049Da, calculated from sequence, including chromophore) and carries a phycocyanobilin pigment covalently linked to Cys84. The p chain contains 172 amino acids (19344Da, calculated from sequence, including chromophores) and carries a phycocyanobilin pigment covalently linked at Cys82 and a phycoerythrobilin pigment at Cys153. A y-N-meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
33
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 91 publications
1
33
0
Order By: Relevance
“…Ducret (Dissertation ETH no. 10731, 1994). 1989; Grossman, 1990;MacColl and Guard-Friar, 1987;Morschel and Rhiel, 1987;Sidler, 1994;Tandeau de Marsac, 1991;Wehrmeyer, 1990;Zuber, 1985Zuber, ,1986Zuber et al, 1987). The most common and best described phycobilisorne belongs to the hemidiscoidal type, which is typically isolated in cyanobacteria.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Ducret (Dissertation ETH no. 10731, 1994). 1989; Grossman, 1990;MacColl and Guard-Friar, 1987;Morschel and Rhiel, 1987;Sidler, 1994;Tandeau de Marsac, 1991;Wehrmeyer, 1990;Zuber, 1985Zuber, ,1986Zuber et al, 1987). The most common and best described phycobilisorne belongs to the hemidiscoidal type, which is typically isolated in cyanobacteria.…”
mentioning
confidence: 99%
“…Hexameric complexes are formed by the aggregation of two trimeric units into a head-to-head configuration (Schirmer et al, 1986 ;Ficner et al, 1992) exhibiting a dimension of 11 nmX 6 nm. Phycobiliproteins may be divided into three main groups by comparing their chromophore compositions, their immunological properties and their amino acid sequences (Zuber, 1985(Zuber, , 1986Glazer, 1987;McColl and Guard-Friar, 1987;Ducret et al, 1994;Sidler, 1994): the phycoerythrins (A,,, = 490-570 nm); the phycocyanins and phycoerythrocyanins (A, , , = 490-625 nm and 560-600 nm, respectively) ; and the allophycocyanins (A, , , = 650-665 nm). Each phycobiliprotein type fulfills a specific function in the phycobilisome as reflected in its distribution in the antenna (Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The methyltransferase reaction pro-duces a highly conserved ␥-N-methylasparagine residue at the ␤-72 position of almost all ␤-subunits isolated from cyanobacteria, red algae, and cryptomonads (17,35,36,45,65). This modification is thought to change the environment of the chromophore at position ␤-82 to minimize the rates of nonradiative energy loss within PBS (59,60).…”
mentioning
confidence: 99%
“…The presence of the unusual post-translational modification, ␥-N-methylasparagine, at the Asn 72 residue of PBP ␤-subunits in most cyanobacteria, red algae, and cryptomonads has been well documented (2,3,7,8). Klotz and Glazer (3) examined a range of cyanobacterial PBP for the release of methylamine after acid hydrolysis and found that PBP ␤-subunits were only rarely unmethylated.…”
Section: Discussionmentioning
confidence: 99%